Tráfico de drogas: uma opção entre escolhas escassas - Ana Amelia Cypreste Faria (2009)
The present work had as its purpose to comprehend the historical, social and economic context of the drugs dealing, as well as the psychosocial aspects which are related to the adhesion to this activity. Through researches carried out at the prison environment, by listening to the life history of people involved in the traffic, we tried to understand the relationship of this context to the individual choice of adhesion to this illegal activity. Understood as a high increasing practice in the world reality, the drug traffic has been shown as a strong phenomenon of recruiting workers, including children, who began their careers at a lower hierarchy position, achieving higher levels due to the increasing of the business or the death of the formers drug dealers. It has been known that in the present historical and economical context, there are lots of contingent of unemployed people or people submitted to precarious working conditions, as a result of the competences required by the new liberal economic order that excludes from the labor market an enormous layer of the population without conditions of facing them and without perspective of changes. So, there has been a situation of social exclusion with structural dimensions, as it hasnt been related to a punctual crisis, but to a world context where the social aspects are subsumed under the economic ones. Such social exclusion is followed by a citizenship one, because the state, also submitted to the mercantilism rules, neglects its role of welfare state, leaving the social excluded people without protection and without the access to the citizens rights. Besides this, there is the consumist seduction that, in spite of the individual acquisition power, develops an urgent possession sense that means success achievement, creating an illusion of power and social recognizing that comes from what can be possessed. In this fertile environment, the drugs dealing , has been shown as an economic activity that presents itself as an opportunity of inclusion in the capitalist world, in a marginal way, because of its illegality and morality questioned by society. Its way of functioning inside the marginality, has been characterized in an extremely peculiar way, though it follows some business principles of production and selling adopted by many companies legally placed in the business world. So, this research showed that the traffic of drugs is an option to be included, even if in a perverse way, an option that has to be done in spite of all risks, among limited choices characterized by the social, economical and political context.